Designing Metal Phosphide Solid-Electrolyte Interphase for Stable Lithium Metal Batteries Through Electrified Interface Optimization and Synergistic Conversion - Jung Been Park; Changhoon Choi; Min Sang Kim; Hyeongbeom Kang; Eunji Kwon; Seungho Yu; Dong-Wan Kim (Nano-Micro Letters)
Highlights Through strategic heterostructure design, it is possible to create electrified interfaces that induce the formation of a fully ionized depletion region and a built-in electric field. These electrified interfaces enhance Li affinity and promote uniform current distribution, leading to stable Li deposition behavior. Owing to intentional design, SnP0.94/CoP heterostructure enables in situ conversion to a mixed ionic/electronic conductor during cycling, ensuring the long lifespan.